Grouting prediction based on analytical and numerical approaches - Xiao, Fei (2019)
Rock masses are discontinuous, due to the existence rock fractures, like faults, cracks, joints, and other similar geological features, which could not only affect the structural strength, but also provide interconnected channels for water inflow. The discontinuities in rock mass pose a great threat to rock excavation, and could lead to economic loss or even casualties, if they are not properly handled. One way to improve the rock mass quality is grouting, which helps to seal those discontinuities, and strengthen the rock mass simultaneously. However, the grouting cost accounts for a considerable percentage of the total cost for construction of underground facilities, especially for rock masses with complex geological conditions. One reason for the high cost is that the stop criteria cannot be properly determined, which is normally based on either empirical criteria or experience; moreover, the accuracy of existing methods for grouting simulation is poor, due to the lack of effective theoretical models and insufficient consideration of geological conditions. A lot of practical factors should be considered to better model the grouting process, including the influence of fracture deformation (referring to normal deformation in this thesis) and flowing water, the existence of interconnected fracture network, and fracture roughness and tortuosity. Previous work on grouting investigation is summarized in the thesis, introducing fundamental information on grouting technology, including characteristics of rock masses and cement grout; existing theoretical and empirical models used for grouting prediction; and some basic concepts related to grouting practice. For grout flow in rock fractures not directly intersected by the injection hole, channel flow can represent the grout flow, a one-dimensional (1D) model with grout flow within two parallel plates. This model is very useful and popular, due to its simplicity and its application in evaluating laboratory testing data. The governing equation for the 1D grouting model is derived analytically, and numerical algorithm is developed for solving the corresponding equations. Two different methods are defined under two boundary conditions: constant injection pressure or constant injection rate, as the corresponding algorithms for equation solving are significantly different. Thereafter, the characteristics of grout penetration using the two methods are discussed. For rock fractures directly intersected by the injection hole, the distribution of cement grout around the injection hole is in radial direction, which is two-dimensional (2D). Therefore, a governing equation for radial grout penetration initiating from the injection hole is derived. Real time grout penetration within two neighboring fractures directly intersected by the injection hole is calculated based on numerical algorithm, and the influence of fracture deformation (normal deformation) induced by grout pressure on the penetrability of rock fracture with smaller aperture is analyzed. Then, an analytical model is proposed to predict grouting of single rock fracture with flowing water based on the theory of potential flow, which is used for explaining the data obtained from grouting test in the laboratory considering flowing water. A module for predicting grout penetration in a 2D fracture system is developed based on the Discontinuous Deformation Analysis (DDA), which can present good visualization of real-time grout penetration in intersected rock fractures and real-time pressure variation at various intersection nodes. Finally, the influence of fracture roughness on grout penetration and fluid transportation is investigated based on laboratory test and numerical simulation. Most existing models take rock fractures as two smooth parallel plates, neglecting the characteristics of fracture surfaces, like fracture roughness, which, however, do exist and can have substantial impact on fluid flow within real rock fractures. Therefore, with assistance of 3D printing, large scale rock fracture with rough surfaces are generated and used for grouting test in laboratory, which are compared with grouting test using traditional fracture channel with smooth parallel surfaces. It is found from the laboratory test results that the impact from fracture roughness is considerable, so the influence is further investigated with numerical simulations.